Bone forming ability of recombinant human collagen peptide granules applied with β‐tricalcium phosphate fine particles. Issue 7 (9th May 2020) - Furihata, Tomokazu; Miyaji, Hirofumi; Nishida, Erika; Kato, Akihito; Miyata, Saori; Shitomi, Kanako; Mayumi, Kayoko; Kanemoto, Yukimi; Sugaya, Tsutomu; Akasaka, Tsukasa
Abstract: Recombinant human collagen peptide, developed based on human collagen type I, contains an arginyl‐glycyl‐aspartic acid (RGD)‐rich motif to enhance cell behavior and is anticipated as a xeno‐free polymer material for use in tissue engineering. We fabricated granules containing recombinant human collagen peptide (RCP) applied with beta‐tricalcium phosphate fine particles (RCP/β‐TCP) as bone filling scaffold material and assessed the bone forming ability of RCP/β‐TCP. Recombinant peptide was thermal crosslinked and freeze‐dried to prepare RCP. An aqueous dispersion of β‐TCP fine particles was added to RCP to obtain RCP/β‐TCP. Subsequently, RCP/β‐TCP were characterized using scanning electron microscopy (SEM), energy dispersive X‐ray spectrometry (EDX), and cell culture assessments. Furthermore, RCP/β‐TCP were implanted into rat cranial bone defects for radiographic and histological evaluations. In SEM and EDX analyses of RCP/β‐TCP, β‐TCP particles dose‐dependently covered the surface of RCP. Cell culture tests showed that RCP/β‐TCP remarkably promoted proliferation and mRNA expression of various genes, such as integrin β1 and osteogenic markers, of osteoblastic MC3T3‐E1 cells. Histomorphometric assessment at 4 weeks showed that RCP/β‐TCP significantly promoted new skull bone formation compared to RCP ( p  < 0.05) and control (no application) ( p  < 0.01). Accordingly, these findings suggest RCP/β‐TCP possess bone forming capability and would be beneficial for bone tissue engineering therapy.